Вы находитесь на странице: 1из 16

Mathematics

III Lecture
Notes

Laplace
Transforms
Revision Mathematics III
Why Laplace
Transforms?
Definition (First
Principles)
Lecture Notes
Table of
Standard Forms
The Linearity
Property
Examples
Solutions
Laplace Transforms
Three Theorems
Proofs of
Theorems
Examples using
Theorems

Durban University of Technology

Prof D Day

Mathematics
III Lecture
Notes
Outline
Laplace
Transforms
Revision
Why Laplace
Transforms?
Definition (First 1 Laplace Transforms
Principles)
Table of
Standard Forms
Revision
The Linearity
Property Why Laplace Transforms?
Examples
Solutions Definition (First Principles)
Three Theorems
Proofs of Table of Standard Forms
Theorems
Examples using
Theorems
The Linearity Property
Examples
Solutions
Three Theorems
Proofs of Theorems
Examples using Theorems
Mathematics
III Lecture
Notes
Revision
Laplace
Transforms
Revision
Why Laplace
Transforms? You will need to revise;
Definition (First
Principles)
Table of
Standard Forms
1 Complex Numbers and Hyperbolic Functions
The Linearity
Property 2 The Binomial Theorem
Examples
Solutions
Three Theorems
3 Lhospitals Rule
Proofs of
Theorems 4 All Trigonometric and Hyperbolic identities and
Examples using
Theorems

5 Integration, particularly:
Integration by Parts and

Integration using Partial Fractions

Mathematics
III Lecture
Notes
Revision
Complex Numbers
Laplace
Transforms
Revision
Why Laplace
Transforms?
Definition (First
Principles)
z = x + jy (Rectangular Form)
Table of
Standard Forms = r (cos + j sin ) = r (Polar Form)
The Linearity
Property
Examples = re j (Exponential Form)
Solutions
Three Theorems
Proofs of
Theorems
Examples using
Theorems
Hence;

e j = cos + j sin = cis =

and

cos =Re{e j }
sin =Im{e j }
Mathematics
III Lecture
Notes
Revision
Hyperbolic Functions and Binomial Theorem
Laplace
Transforms Hyperbolic Functions
Revision
Why Laplace e at + e at
Transforms?
Definition (First
cosh at =
Principles) 2
e e at
at
Table of
Standard Forms
The Linearity
Property
sinh at =
Examples 2
Solutions
Three Theorems Binomial Theorem
Proofs of
Theorems n(n1) n2 2
Examples using
Theorems
(a + b)n = an + nan1 b + 2! a b + + bn
for n Z+
/ Z+ {0} then the series is infinite
If n
n(n1) n2 2
(a + b)n = an + nan1 b + 2! a b +
therefore
(1 x)1 = 1 + x + x 2 + x 3 + x 4 + and
(1 + x)1 = 1 x + x 2 x 3 + x 4 +

Mathematics
III Lecture
Notes
Revision
Lhospitals Rule
Laplace
Transforms
Revision
Why Laplace
Transforms? Given functions f (t) and g (t), differentiable on an open
Definition (First
Principles)
Table of
interval containing a,
Standard Forms
The Linearity if
Property
Examples
Solutions
1 lim f (t) = lim g (t) = 0,
Three Theorems
ta ta
Proofs of
Theorems f 0 (t)
Examples using 2 lim exists, and
Theorems ta g 0 (t)

3 g 0 (t) 6= 0 for all t 6= a on the open interval, Then

f (t) f 0 (t)
lim = lim 0
ta g (t) ta g (t)
Mathematics
III Lecture
Notes
revision
Trigonometric and Hyperbolic Identities
Laplace
Transforms Trigonometric Identities
Revision
Why Laplace sin (A) = sin A cos2 A + sin2 A = 1
Transforms?
Definition (First cos (A) = cos A sin 2A = 2 sin A cos A
Principles)
Table of tan (A) = tan A cos 2A = cos2 A sin2 A
Standard Forms
The Linearity = 2 cos2 A 1
Property
Examples = 1 2 sin2 A
Solutions
Three Theorems
Proofs of Osbornes Rule: A trigonometry identity can be converted to an
Theorems
Examples using analogous hyperbolic identity, by exchanging trigonometric functions
Theorems
with their hyperbolic counterparts, and then changing the signs of
terms containing the product of two hyperbolic sines.
Hyperbolic Identities
sinh (A) = sinh A cosh2 A sinh2 A = 1
cosh (A) = cosh A sinh 2A = 2 sinh A cosh A
tanh (A) = tanh A cosh 2A = cosh2 A + sinh2 A
= 2 cosh2 A 1
= 1 + 2 sinh2 A

Mathematics
III Lecture
Notes
revision
Trigonometric and Hyperbolic Identities
Laplace
Transforms
Revision
Why Laplace Trigonometric Identities
Transforms?
Definition (First
Principles) sin(A + B) = sin A cos B + cos A sin B
Table of
Standard Forms
The Linearity
Property
sin(A B) = sin A cos B cos A sin B
Examples
Solutions cos(A + B) = cos A cos B sin A sin B
Three Theorems
Proofs of
Theorems cos(A B) = cos A cos B + sin A sin B
Examples using
Theorems

Hyperbolic Identities
sinh(A + B) = sinh A cosh B + cosh A sinh B
sinh(A B) = sinh A cosh B cosh A sinh B
cosh(A + B) = cosh A cosh B + sinh A sinh B
cosh(A B) = cosh A cosh B sinh A sinh B
Mathematics
III Lecture
Notes
revision
Trigonometric and Hyperbolic Identities
Laplace
Transforms
Revision Trigonometric Identities
Why Laplace
Transforms?
Definition (First
sin2 A = 12 (1 cos 2A)
Principles)
Table of
Standard Forms
cos2 A = 21 (1 + cos 2A)
The Linearity
Property sin A cos B = 12 [sin(A + B) + sin(A B)]
Examples
Solutions
Three Theorems
sin A sin B = 12 [cos(A B) cos(A + B)]
Proofs of
Theorems cos A cos B = 12 [cos(A + B) + cos(A B)]
Examples using
Theorems

Hyperbolic Identities
sinh2 A = 12 (cosh 2A 1)
cosh2 A = 21 (cosh 2A + 1)
sinh A cosh B = 12 [sinh(A + B) + sinh(A B)]
sinh A sinh B = 12 [cosh(A + B) cosh(A B)]
cosh A cosh B = 12 [cosh(A + B) + cosh(A B)]

Mathematics
III Lecture
Notes
Why Laplace Transforms?
Laplace
Transforms
Revision
Why Laplace
Transforms?
Definition (First
Laplace Transforms provide an effective method for solving
Principles)
Table of many practical problems in science and engineering
Standard Forms
The Linearity
Property
Examples
Solutions
Three Theorems
Proofs of
We will use laplace Transforms to solve Differential
Theorems
Examples using Equations with constant coefficients a1 , a2 , a3 , , an , of
Theorems
the form:-

d ny d n1 y dy
a1 n + a2 n1 + + an1 + an y = g (t)
dt dt dt
Mathematics
III Lecture
Notes
Laplace Transforms
Definition (First Principles)
Laplace
Transforms
Revision
If f (t) is defined for all t > 0, then the Laplace Transform of
Why Laplace
Transforms?
f (t) is defined by:-
Definition (First
Principles)
Table of
Z
Standard Forms
The Linearity
Property
L {f (t)} = e st f (t)dt = F (s)
Examples 0
Solutions
Three Theorems
Proofs of NoteZ
Theorems Z a
st
e st f (t)dt
Examples using
Theorems 1 e f (t)dt = lim
0 a 0
2 The parameter s is complex and the real part of s, Re(s)
is sufficiently large in order to ensure that the integral
converges (i.e that the limit in note 1 above, exists).
3 In some texts p is used in place of s as a parameter. This
is done to prevent s being confused with the number 5
4 L {f (t)} is a function of s, i.e L {f (t)} = F (s)

Mathematics
III Lecture
Notes
A table of standard Laplace Transform can be derived using the
definition of the Laplace Transform (First Principles)
Laplace
Transforms

L {f (t)} = F (s)
Revision
Why Laplace
Transforms?
f (t)
Definition (First
Principles) a
Table of
Standard Forms
a (constant) s
The Linearity
Property
Examples e at 1
s+a
proof
Solutions
Three Theorems
n!
Proofs of
Theorems
tn s n+1
proof

Examples using
Theorems a
sin at s 2 +a2
proof

s
cos at s 2 +a2
a
sinh at s 2 a2
s
cosh at s 2 a2
proof
Mathematics
III Lecture
Notes
First Principles
L {e at }
Laplace
Transforms Z
L {e at } e st e at dt
Revision
Why Laplace =
Transforms?
Definition (First
0
Principles)
Table of
Z
Standard Forms
The Linearity = e (s+a)t dt
Property
Examples
0
Solutions  
Three Theorems 1
Proofs of
Theorems = e (s+a)t
Examples using s +a 0
Theorems

1
= [ lim e (s+a)t e (s+a)(0) ]
s + a t
1
= [ 0 1]
s +a
1
= Back to table
s +a

Mathematics
III Lecture
Notes
First Principles
L {t n }
Z
st n
Laplace
Transforms
L {t n } = e t dt
(Integration by Parts)
Revision 0 n 
n st n1
Z
Why Laplace t st
Transforms?
= e + e t dt
Definition (First
Principles) s Z 0 s 0
Table of
Standard Forms n st n1 n
The Linearity =0+ e t dt = L {t n1 }
Property
Examples
s 0 s
n
L {t n } = L {t n1 }
Solutions
Three Theorems
Proofs of
Theorems
s  
n n1
L {t n2 }
Examples using
Theorems =
s s
..
.
 
n n1 n2 2 1
= L {t 0 }
s s s s s
n n1 n2 2 1 1
=
s s s s s s
n!
= n+1 Back to table
s
Mathematics
III Lecture
Notes
First Principles
L {sin at}
Laplace Z
Transforms
Revision
L {sin at} = e st sin at dt (By Parts or Complex Nos.)
Why Laplace
Transforms? Z0
e st [Im{e jat }]dt
Definition (First
Principles)
Table of
=
Standard Forms 0
The Linearity
Z
e (sja)t dt
Property
Examples = Im
Solutions
Three Theorems "0 #
Proofs of
Theorems e (sja)t
Examples using = Im
Theorems
s ja
 0   
0 1 1
= Im + = Im
s ja s ja s ja
   
s + ja s + ja
= Im = Im 2
(s ja)(s + ja) s + a2
 
s a a
= Im 2 + j =
s + a2 s 2 + a2 s 2 + a2
Back to table

Mathematics
III Lecture
Notes
First Principles
L {cosh at}
Laplace
Transforms
Z
Revision L {cosh at} = e st cosh at dt
Why Laplace
Transforms?
Definition (First
Z 0  at at

e + e
e st
Principles)
Table of = dt
Standard Forms
The Linearity 0 2
1 (sa)t
Property Z
+ e (s+a)t dt
Examples
Solutions = e
Three Theorems 2 0
Proofs of " #
Theorems
Examples using 1 e (sa)t e (s+a)t
Theorems
=
2 s a s +a
  0 
1 0 0 1 1
=
2 s a s +a s a s +a
 
1 2s
=
2 (s a)(s + a)
s
= 2 2
Back to table
s a
Mathematics
III Lecture
Notes
The Linearity Property and
Laplace
Examples using Standard Forms
Transforms
Revision
Why Laplace
The Linearity Property
Transforms?
Definition (First
Principles)
Table of L {c1 f (t) + c2 g (t)} = c1 L {f (t)} + c2 L {g (t)}
Standard Forms
The Linearity
Property
Examples Examples
Solutions

1 L 3 4t + e
3 5t

Three Theorems
Proofs of
sin 3t + cosh 4t go to solution
Theorems
2 L (sinh t cosh t)2

Examples using go to solution
Theorems

3 L 3 sin 2t
2

go to solution

4 L {4 sin 2t sin 3t} go to solution

5 L {4 sinh[2(t + 3)]} go to solution

Tutorial Questions
1 L {t 2 + 4t 6 + sinh2 2t}
2 L {e t sinh2 2t} (Hint: Use Exponential form of sinh 2t)

Mathematics
III Lecture
Notes

1) L 3 4t 3 + e 5t sin 3t + cosh 4t

Laplace
Transforms
Revision
Why Laplace
Transforms?
Definition (First
Principles)
= L {3} 4L {t 3 } + L {e 5t } L {sin 3t} + L {cosh 4t}
Table of
Standard Forms
The Linearity 3 3!
 1 3 s
Property
Examples
= s 4 s4
+ s+5 s 2 +9
+ s 2 16
Solutions
Three Theorems
Proofs of 3 24 1 3 s
Theorems = s s4
+ s+5 s 2 +9
+ s 2 16
Examples using
Theorems

back to examples
Mathematics
2) L (sinh t cosh t) 2

III Lecture
Notes

Laplace
Transforms
= L {sinh2 t 2 sinh t cosh t + cosh2 t}
Revision
Why Laplace
Transforms?
Definition (First
= L {cosh 2t sinh 2t}
Principles)
Table of
Standard Forms
The Linearity
Property
= L {cosh 2t} L {sinh 2t}
Examples
Solutions
Three Theorems
s 2
Proofs of
Theorems
= s 2 4 s 2 4
Examples using
Theorems

s2
= s 2 4

1
= s+2

back to examples

Mathematics
III Lecture
Notes

3) L 3 sin2 2t


Laplace
Transforms

= L 3 12 (1 cos 4t)
Revision
  
Why Laplace
Transforms?
Definition (First
Principles)
Table of
Standard Forms = 32 L (1 cos 4t)
The Linearity
Property
Examples
Solutions = 32 (L {1} L {cos 4t})
Three Theorems
Proofs of
Theorems h i
Examples using
3 1 s
Theorems
= 2 s s 2 +16

back to examples
Mathematics
III Lecture
Notes

4) L {4 sin 2t sin 3t}


Laplace
Transforms

= 4 L {sin 2t sin 3t}


Revision
Why Laplace
Transforms?
Definition (First
Principles)

=4L
1
2 [cos(t) cos(5t)]
Table of
Standard Forms
The Linearity
Property
Examples
Solutions
Three Theorems
= 2 L {cos t cos 5t}
Proofs of
Theorems h i
Examples using
s s
Theorems =2 s 2 +1
s 2 +25

back to examples

Mathematics
III Lecture 5) L {4 sinh[2(t + 3)]}
Notes

Laplace = 4L {sinh(2t + 6)}


Transforms
Revision
Why Laplace
Transforms?
Definition (First
= 4L {sinh 2t cosh 6 + cosh 2t sinh 6}
Principles)
Table of
Standard Forms
The Linearity
Property
= 4 cosh 6L {sinh 2t} + 4 sinh 6L {cosh 2t}
Examples
Solutions    
Three Theorems 2 s
Proofs of
= 4 cosh 6 + 4 sinh 6
Theorems
Examples using s2 4 s2 4
Theorems

8 cosh 6 (4 sinh 6)s


= +
s2 4 s2 4

8 cosh 6 + (4 sinh 6)s


=
s2 4

back to examples
Mathematics
III Lecture
Notes
Three Theorems
Laplace
Transforms
Theorem 1 (First Shift Theorem) go to Proof

Revision If L {f (t)} = F (s) then


Why Laplace
Transforms?
Definition (First  at
L e f (t) = F (s + a)
Principles)

Table of
Standard Forms
The Linearity
Property
Examples Theorem 2 (Multiplication by t n ) go to Proof
Solutions
Three Theorems
Proofs of
dn
L {t f (t)} = (1) n F (s)
Theorems n n
Examples using
Theorems
ds
Theorem 3 (Dividing
  by t)
f (t)
Provided lim exists
t0 t
  Z
f (t)
L = F ()d
t s

Mathematics
III Lecture
Notes
Three Theorems
Laplace
Transforms
Theorem 1 (First Shift Theorem)
Revision If L {f (t)} = F (s) then
Why Laplace
Transforms?
Definition (First
at
L e
Principles)

Table of f (t) = F (s + a)
Standard Forms
The Linearity
Property
Examples
Solutions
Proof
Three Theorems
Z
L {e at f (t)} e st e at f (t) dt
 
Proofs of
Theorems
=
Examples using
Theorems Z0
= e (s+a)t f (t) dt
0
= F (s + a) (definition of L {f (t)})

Back to Theorems
Mathematics
III Lecture Theorem 2 (Multiplication by t n )
Notes

dn
Laplace L {t f (t)} = (1) n F (s)
n n
Transforms
Revision
ds
Why Laplace
Transforms?
Definition (First
Principles)
Proof
Table of
Z
Standard Forms
The Linearity
L {t n f (t)} = e st t n f (t)dt
Property
Examples Z0
Solutions d n st n
Three Theorems = (1) n
(e )f (t)dt
Proofs of
Theorems 0 ds
Examples using
dn st ) = (1)n t n e st
Theorems [since ds n (e

and (1)n = (1)n for all n]


d n Z
= (1)n n e st f (t)dt
ds 0
n dn
= (1) F (s)
ds n

Back to Theorems

Mathematics
III Lecture
Notes
Examples using Theorems
Laplace
Transforms
Revision
Why Laplace
Transforms?
L e 3t t 2 using Theorem 1 and Theorem 2

Definition (First go to solution
Principles) 1
Table of
Standard Forms
The Linearity
Property
Examples
Solutions
Three Theorems

L
Proofs of
 sinh 2t
Theorems 2 go to solution
Examples using t
Theorems

L te 2t cos 3t

3 go to solution
1) L e 3t t 2

Mathematics
III Lecture
Notes

Theorem 1 [L {e at f (t)} = F (s + a)]


Laplace
2!
Transforms
Revision
Let f (t) = t 2 then F (s) = s3
, then
Why Laplace
2!
Transforms?
Definition (First
F (s + a) = F (s + 3) = (s+3) 3
Principles)

Thus L e 3t t 2 = 2!
Table of

Standard Forms
The Linearity
(s+3)3
Property
Examples
Solutions d n
Three Theorems Theorem 2 [L {t n f (t)} = (1)n ds n F (s)]
Proofs of
Theorems
Examples using Let f (t) = e 3t , then F (s) = s+31
Theorems

L e t =L e t
 3t 2  3t 2
 
2 d2 1
= (1) ds 2 s+3
 
d 1
= ds (s+3)2
2
= (s+3)3

Back to examples

Mathematics
2) L
III Lecture
 sinh 2t
Notes t

sinh 2t 2 cosh 2t 2 cosh 0


 
Laplace limt0 t= limt0 1 = 1 =2
Transforms
Revision the limit exists
Why Laplace
Transforms?
Definition (First
Z
2
L
Principles)  sinh 2t
Table of
t = d
Standard Forms
The Linearity s 2 4
Property
Examples
h  i
1 2
Solutions
Three Theorems
= 2 ln +2
Proofs of
s
Theorems   
Examples using
1 2
 
Theorems 1 1 s2
= lim 2 ln 1+ 2
ln2 s+2

  1
1 s2 2
= 2 ln 1 + ln s+2
q
s+2
= ln s2

Back to examples
Mathematics
III Lecture
Notes
3) L te cos 3t
 2t
(First method)
Laplace
Transforms
Revision
Use mainly theorem 1 with theorem 2 as a sub problem
Why Laplace
Transforms?
L te 2t cos 3t = L e 2t (t cos 3t)
 
Definition (First
Principles)
theorem 1
Table of
Standard Forms
The Linearity
Property Let f (t) = t cos 3t then
Examples
d
Solutions
Three Theorems
F (s) = (1)1 ds (L {cos 3t}) theorem 2
Proofs of   2 +9s(2s)
s 2 9
= ds s 2 +9 = s (s
d s
Theorems
Examples using 2 +9)2 = (s 2 +9)2
Theorems

(s2)2 9
L te 2t cos 3t = F (s + a) = F (s 2) =

[(S2)2 +9]2

Back to examples

Mathematics
3) L te 2t cos 3t

III Lecture (Second method)
Notes

Use mainly theorem 2 with theorem 1 as a sub problem


Laplace
Transforms
L t(e 2t cos 3t)

Revision theorem 2
Why Laplace
Transforms?
Definition (First
Principles)
Table of Let f (t) = e 2t cos 3t and g (t) = cos 3t Theorem 1
Standard Forms
The Linearity
Property Then G (s) = L {g (t)} = s
s 2 +9
and
Examples
Solutions
Three Theorems
L {f (t)} = L {e 2t cos 3t} = G (s + a) = G (s 2)
Proofs of s2
Theorems
Examples using
= (s2)2 +9
Theorems

 
L te cos 3t = (1) ds (s2)2 +9
d s2
 2t 1

2
= (s2) [(s2)
+9(s2)2(s2)
2 +9]2

(s2)2 9
= [(s2)2 +9]2

Back to examples
Mathematics
III Lecture
Notes
Tutorial Problems
Laplace
Transforms
Revision
Why Laplace
Transforms?
Definition (First
Principles)
Table of
Standard Forms Stroud:
The Linearity
Property
Examples
Laplace Transforms 1:
Solutions
Three Theorems
Proofs of
Frame 92; 1(a) - (f)
Theorems
Examples using
Theorems Frame 93; 1(a) - (f)

Course Handout; Laplace Transforms Extra Tut